Mineral nutrient uptake and removal by cowpea, soybean and maize cultivars in West Africa, and implications for carbon cycle effects on soil acidification - Randall, P.J.; Abaidoo, Robert C.; Hocking, PJ; Sanginga, Nteranya (Cambridge University Press, 2006)
A field study of cowpea, soybean and maize was made at Ibadan, Nigeria, to determine the uptake of mineral nutrients and quantities removed in crop residues and seed. Concentrations of N, the major cations (K, Ca, Mg and Na) and major anions (P, S and Cl), and the micronutrients (Fe, Mn, Zn and Cu) were determined in shoots harvested at flowering and maturity. Concentrations of excess cations in shoots at flowering were 135 cmolc kg?1 for soybean, 158 cmolc kg?1 for cowpea and 58 cmolc kg?1 for maize. In crop residues and seed at maturity, the values decreased to 75 and 56 cmolc kg?1 respectively for soybean, 68 and 27 cmolc kg?1 respectively for cowpea, and 52 and 10 cmolc kg?1 respectively for maize. Nutrient and excess cation concentrations were also measured in 13 soybean and eight cowpea lines grown in replicated field trials at Fashola in the derived savanna zone and Shika in the northern Guinea savanna zone of Nigeria to assess the variation within these species. Maize, mucuna and lablab were included at these sites. The results are discussed in the context of soil nutrient depletion due to removal of nutrient elements in harvested seed and stover. The contribution of seed and stover removal to the proton (H+) budget and acidification of the soil is also discussed. It is estimated that the quantity of lime required to neutralize the acidity resulting from the removal of 1 t seed is 28 kg for soybean, 14 kg for cowpea and 5 kg for maize. The corresponding values for stover were soybean 35, cowpea 24 and maize 26 kg lime t?1 stover. Given the soil pH buffer capacity at the Ibadan site for the surface 16 cm, the yields obtained and assuming that seed and crop residues are removed, carbon cycle acidification would lead to a fall of 1 pH unit after 75 crops for soybean, 114 crops for cowpea and 68 crops for maize. The inclusion of legumes in cropping systems to increase N supply, and the use of P fertilizer to maximize N-fixation by legumes will raise production, but will inevitably accelerate removal of alkalinity and nutrients in harvested products, and the consequent decline in soil fertility. The data presented in this paper can be used in estimating the lime and fertilizer nutrients needed to maintain soil fertility and sustain yields.